2018
DOI: 10.5603/gp.a2018.0052
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of GWAS — identified polymorphisms associated with infertility risk in Polish women with endometriosis

Abstract: Our results demonstrate association of RAF of rs12700667 and rs4141819 SNPs with infertility in Polish women with advanced endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
1
10
0
1
Order By: Relevance
“…8,13 However, other replication studies found correlation between the referred polymorphism and endometriosis in Chinese and Polish populations, as well as the meta-analysis that included GWAS in a Belgian population. 12,14,15 Thus, our results corroborate the majority of previous studies, suggesting that the rs12700667 is relevant to the development of endometriosis not only in European and Asian populations, but also in a highly admixed population such as the Brazilian.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…8,13 However, other replication studies found correlation between the referred polymorphism and endometriosis in Chinese and Polish populations, as well as the meta-analysis that included GWAS in a Belgian population. 12,14,15 Thus, our results corroborate the majority of previous studies, suggesting that the rs12700667 is relevant to the development of endometriosis not only in European and Asian populations, but also in a highly admixed population such as the Brazilian.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, a recent study with a Polish sample of 315 infertile women with endometriosis and 406 healthy fertile women did not find any differences in the distribution frequencies of this polymorphism between the groups. 14 In 2010, the GWA study by Adachi et al validated an important association between endometriosis and A > G (rs13394619) polymorphism in the GREB1 gene of the 2p25.1 chromosome (OR ¼ 1.35; 95%CI¼ 1.06-1.18; p ¼ 3.8 Â 10 À5 ). 16 In 2012, this association was also found (OR ¼ 1.12; 95%CI ¼1.06-1.18; p ¼ 2.1 Â 10 À5 ) in the meta-analysis that comprehended Japanese and European populations.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies on endometriosis have demonstrated an association between susceptibility to the disease and markers located in or near the WNT ligand WNT4 gene encoding for a noncanonical key player in the development of the female reproductive tract [57]. Mafra et al studied the relationship between endometriosis and four WNT4 SNPs, suggesting that two SNPs (rs16826658 and rs3820282) of the WNT4 gene might be involved in the pathogenesis of endometriosis in infertile women (Table 1) [58].…”
Section: The Wnt Pathway Between Genetics and Inflammationmentioning
confidence: 99%
“…Osinski et al attempted to validate the GWAS results for 10 significant SNPs from the seminal analyses on a cohort smaller than the ones initially used (315 endometriosis and 406 healthy fertile women as controls) and could overall confirm rs12700667 near NFE2L3, and rs4141819 near ETAA1, for the infertile women with stages III/IV [ 47 ]. In the initial study [ 55 ], the OR associated with rs4141819 was estimated at 1.22 for the risk allele, and at 1.20 for rs12700667.…”
Section: Replication Studiesmentioning
confidence: 99%